STRATEGI PENGEMBANGAN PADI ORGANIK DI KABUPATEN TRENGGALEK PROVINSI JAWA TIMUR - Chitra Shinta Wardhani; Abu Talkah; Supriyono Supriyono (Manajemen Agribisnis: Jurnal Agribisnis, 2020)
Trenggalek is a regency in East Java province which has potential and has run organic rice farms. But this effort is still encountering a variety of obstacles and barriers. Therefore, it is necessary to do research on development strategy of organic rice. The study was conducted from March until May 2017 in Farmers Group Ngudi Makmur, Cakul village, Dongko sub-district with the consideration that the area is an area that is developing organic rice. This type of research is a descriptive research. The sampling method is purposive sampling, where samples are taken from rice fields of farmers implementing organic rice. The data collected are primary data and secondary data. Primary data was collected by the method of data collection using interviews, questionnaires and observation method. The method of data analysis is to identify the internal factors using IFAS method, while to identify the external factors by using EFAS. Furthermore, SWOT analysis is used to formulate alternative organic rice development strategy. The last method, quantitative calculation is applied to determine the decisions related to development strategy used. Based on the analysis, the major strength of organic rice development is the importance of health awareness. The critical weakness found in the analysis is that the market is still limited. The dominant opportunity is supportive agro-ecology for the organic rice. The existence of pests is the fundamental threat. The next step is development strategy of organic rice in Trenggalek. The development strategy used are implementing the strength-opportunities (SO) strategy which uses internal strength to take advantage of the opportunities which exist, that is by maintaining and improving the quality of organic products in accordance with SNI by maximizing the coaching by officers of agriculture and maximizing supervision by the Internal Control System (ICS), increasing the productivity of organic rice, expanding the area of organic rice fields and expanding marketing.